2014
DOI: 10.2320/matertrans.mg201404
|View full text |Cite
|
Sign up to set email alerts
|

Dehydriding Property of NaBH<sub>4</sub> Combined with Mg<sub>2</sub>FeH<sub>6</sub>

Abstract: The dehydriding property of xNaBH 4 + (1 ¹ x) Mg 2 FeH 6 (x = 0.10.75) is measured to investigate the effect of combining with complex hydride Mg 2 FeH 6 on reducing dehydriding temperature of metal borohydrides, which has lately been found to be effective for LiBH 4 . When x = 0.1 and 0.125, a single-step dehydriding reaction is observed, while in the composition range x ² 0.25, a multi-step dehydriding reaction is observed. Despite the different dehydriding process, X-ray diffraction measurements confirmed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…The 2:1 mixture also showed multiple thermal transitions together with hydrogen release and it can be seen that as the content of Mg 2 FeH 6 increased, the number of thermal transitions for desorption decreased. This behavior is in agreement with Li et al 13,14 where similar mixtures of Mg 2 FeH 6 þ LiBH 4 and Mg 2 FeH 6 þ NaBH 4 were decomposed under the same conditions and this resulted in the desorption temperatures occurring between that of the individual hydrides. It is important to note that TG data (Figure 1(b)), associated with the thermal events of the Mg(BH 4 ) 2 mixtures in this letter, indicated that each of the ball milled molar ratio combinations was able to desorb close to the aforementioned theoretical capacities, confirming that complete desorption of both the Mg(BH 4 ) 2 and Mg 2 FeH 6 had taken place.…”
supporting
confidence: 91%
“…The 2:1 mixture also showed multiple thermal transitions together with hydrogen release and it can be seen that as the content of Mg 2 FeH 6 increased, the number of thermal transitions for desorption decreased. This behavior is in agreement with Li et al 13,14 where similar mixtures of Mg 2 FeH 6 þ LiBH 4 and Mg 2 FeH 6 þ NaBH 4 were decomposed under the same conditions and this resulted in the desorption temperatures occurring between that of the individual hydrides. It is important to note that TG data (Figure 1(b)), associated with the thermal events of the Mg(BH 4 ) 2 mixtures in this letter, indicated that each of the ball milled molar ratio combinations was able to desorb close to the aforementioned theoretical capacities, confirming that complete desorption of both the Mg(BH 4 ) 2 and Mg 2 FeH 6 had taken place.…”
supporting
confidence: 91%
“…500 °C for NaBH4 to 360 °C for the NaBH4/Mg2NiH4 composite mixture. When Mg2FeH6 is added to NaBH4 the dehydrogenation can become quite complex [46]. A single dehydriding step is observed for xNaBH4 + (1 − x)Mg2FeH6 when x = 0.1 and 0.125, but a multi-step process occurs when x > 0.25.…”
Section: Hydride Destabilizationmentioning
confidence: 97%
“…Furthermore, the formation of stable side products such as Na 2 B 12 H 12 has been also suggested [180]. Under vacuum, the pathway is different and it involves the formation of free Mg and finally free B [181].…”
Section: Nabhmentioning
confidence: 99%